Subjective short-term memory difficulties at ages 50-75 predict dementia risk in a community-based cohort followed over 17 years - Möllers, Tobias; Stocker, Hannah; Perna, Laura; Rujescu, Dan; Holleczek, Bernd; Schöttker, Ben; Brenner, Hermann (Age & ageing, 2022)
Subjective cognitive decline (SCD) is an established precursor of dementia. However, the relationship between SCD and dementia has been mostly studied among people aged 65+. We aimed to assess the association between subjective memory difficulties at ages 50-75 with all-cause dementia and dementia-subtypes in a community-based cohort with long-term follow-up.6,190 individuals (51% female) aged 50-75 years (median age, 62) attending a general health examination (by a total of 684 general practitioners) in Saarland, Germany, in 2000-2002 were recruited for a community-based cohort study. Subjective difficulties regarding short-term and long-term memory were assessed at baseline with two simple yes/no questions. Associations with dementia (−subtypes) diagnoses during 17 years of follow-up were estimated by Cox proportional hazards models.492 participants were diagnosed with dementia during 17 years of follow-up. Participants with short-term memory difficulties were at higher risk to receive incident all-cause dementia and vascular dementia diagnoses both within 0-9 years (age and sex adjusted hazard ratios (aHR), 1.80 and 2.00, respectively) and within 0-17 years (aHR 1.55 and 1.78, respectively) from recruitment (P < 0.05 in all cases). For clinical Alzheimer’s disease, a significant association was only seen within the initial 6 years. There were no associations of long-term memory difficulties with any type of dementia.Subjective difficulties in short-term memory predict both intermediate and long-term risk of vascular and all-cause dementia even among late middle-age adults. These results underline the importance of cardiovascular disease prevention efforts well before old age for maintaining cognitive health.